Pagandeng: Studi Terhadap Aktivitas Ekonomi Pedagang Sayur di Desa Panciro - Abdul Rahman , (PREDESTINASI, 2022)
Abstract: This study aims to determine the beginning of the emergence of pagandeng in Panciro Village, to know the working system of pagandeng in the village, and to find out the socio-economic changes that occurred in the pagandeng community in Panciro Village and to determine the impact of the presence of pagandeng on the economy of the community in Paciro Village. This type of research is a case study using a qualitative descriptive approach. Informants in this study were pagandeng and the community of Panciro Village, Bajeng District, Gowa Regency by using the technique of determining informants with a snowball sampling system. The results of the research obtained from the field indicate that the beginning of the emergence of pagandeng (bicycles) in Panciro Village, which began in the 80s, was initiated by a man who sold chickens from the Galesong area. The working system of mobile vegetable traders is that there are various ways of working, each partner has different and different times and ways of working and the capital used by the partnership is that there are partners who use their own capital and others who use other people's capital. The socio-economic changes that occurred in Pagandeng in Panciro Village are the relationship between Pagandeng and the community, in this case the social interaction is going very well because considering the efficiency of the transportation equipment used by Pagandeng, it allows a lot of time available for social interaction. In addition, from the perspective of the cooperative economy in Panciro Village, not all of them can be categorized as poor families because their income exceeds the minimum wage and some are below the minimum wage. The impact of the presence of pagandeng on the community's economy is to help meet the needs of clothing for the community, expand employment opportunities in the informal sector, encourage increased income for small traders, and help the community's economy..